Marble waste and pig slurry increment soil quality and reduce metal availability in a tailing pond - Zornoza, Raúl (REVISTA TERRA LATINOAMERICANA, 2013)
Tailing ponds pose environmental hazards, such as toxic metals reaching water sources through wind and water erosion and leaching. These abandoned mine sites contain materials with high contents of Feoxyhydroxides, sulfides, and heavy metals. As a consequence, soils have null vegetation and low soil organic matter. In this study, various physicochemical properties, together with microbial biomass carbon and available metals, were measured before and six months after application of marble waste (6.7 kg m-2), raw pig slurry (4.3 L m-2), and solid phase pig slurry (7 kg m-2) as reclamation strategy in a tailing pond in southeastern Spain, to reduce hazards for the environment and human health. Results showed that aggregate stability, pH, organic carbon, total nitrogen, cation exchange capacity, available phosphorus, exchangeable potassium and microbial biomass carbon increased with the application of the amendments, while available metals and metalloid (As, Cd, Pb and Zn) drastically decreased (90-99%). This study confirms the high effectiveness of initial applications of marble wastes together with pig slurry to initialize the recovery of ecosystems in bare mine soils under Mediterranean semiarid conditions.